Plant–arthropod interactions: who is the winner?. (20th December 2017) - Stahl, Elia; Hilfiker, Olivier; Reymond, Philippe
Summary: Herbivorous arthropods have interacted with plants for millions of years. During feeding they release chemical cues that allow plants to detect the attack and mount an efficient defense response. A signaling cascade triggers the expression of hundreds of genes, which encode defensive proteins and enzymes for synthesis of toxic metabolites. This direct defense is often complemented by emission of volatiles that attract beneficial parasitoids. In return, arthropods have evolved strategies to interfere with plant defenses, either by producing effectors to inhibit detection and downstream signaling steps, or by adapting to their detrimental effect. In this review, we address the current knowledge on the molecular and chemical dialog between plants and herbivores, with an emphasis on co‐evolutionary aspects. Significance Statement: This review covers current knowledge on the molecular and chemical dialogue between plants and herbivores, with an emphasis on coevolutionary aspects.